Construction of sampling and interpolating sequences for multi-band signals. The two-band case - Avdonin, Sergei; Bulanova, Anna; Moran, William (Zielona Góra: Uniwersytet Zielonogórski)
Recently several papers have related the production of sampling and interpolating sequences for multi-band signals to the solution of certain kinds of Wiener-Hopf equations. Our approach is based on connections between exponential Riesz bases and the controllability of distributed parameter systems. For the case of two-band signals we derive an operator whose invertibility is equivalent to the existence of a sampling and interpolating sequence, and prove the invertibility of this operator.
Keywords: sampling and interpolation; multi-band signals; Riesz bases; families of exponentials; Wiener-Hopf equations